The Samurai Trilogy Based on a Novel by Eiji Yoshikawa - Inagaki, Hiroshi; Yasumoto, Jun; Yamada, Kazuo; Mifune, Toshiro; Mikuni, Rentaro; Okada, Mariko (Criterion, 2016)
"The Samurai Trilogy", directed by Hiroshi Inagaki and starring the inimitable Toshiro Mifune, was one of Japan’s most successful exports of the 1950s, a rousing, emotionally gripping tale of combat and self-discovery. Based on a novel that's often called Japan's "Gone with the Wind", this sweeping saga fictionalizes the life of the legendary seventeenth-century swordsman (and writer and artist) Musashi Miyamoto, following him on his path from unruly youth to enlightened warrior. With these three films - 1954's Oscar-winning "Musashi Miyamoto", 1955's "Duel at Ichijoji Temple", and 1956's "Duel at Ganryu Island" - Inagaki created a passionate epic that’s equal parts tender love story and bloody action. [Cover]
Keywords: Blu-Ray-Disc